An in vivo cumulative dose-response assay of the myocardial beta-adrenoceptor system - Peterson, J T; Pohorecky, L A (Journal of pharmacological methods, 1987)
This paper describes an in vivo computer-based cumulative dose-response assay of the myocardial beta-adrenoceptor system. The technique involves measuring the ability of isoproterenol, a beta-adrenergic agonist, administered through a jugular catheter to increase heart rate in rats. The computer system monitors heart rate, provides real-time graphics of incoming data and a detailed graphic review of responses following testing, coordinates drug injections by the experimenter, performs a nonlinear line analysis to determine the dose required to produce 50% maximal responding (ED50) following the data review, and generates a diskette and printer report at the completion of testing. Data are presented and discussed on how well this system meets the assumptions underlying the cumulative dose-response methodology. The results of a study on the effect of acute footshock on the myocardial beta-adrenoceptor system as measured by this technique is also presented and discussed. This technique permits chronic studies of an important myocardial receptor system and allows receptor changes to be tracked within individual subjects.